The Psychological Benefits of Team Sports for College Students - Prasad Kumar G.C.; Dr. Chandrasen U Saruk (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Team sports play a vital role in the college experience, offering students opportunities for personal growth, social interaction, and mental well-being. Colleges provide a structured environment where students can participate in various team sports such as basketball, soccer, volleyball, and cricket, either through official college teams, intramural leagues, or informal recreational activities. These sports promote teamwork, discipline, and a sense of community among students, making them an essential component of college life.